Urbanisation and economic development in India - Daspattanayak, Pritirekha (New Delhi : Rajat Publications, 2000)
Study conducted in Punjab and Orissa.
Includes bibliographical references and index.
Keywords: Urbanization -- India -- Punjab -- Case studies; Urbanization -- India -- Odisha -- Case studies; Punjab (India) -- Economic policy -- Case studies